Analysis of Results of Monitoring and Prediction of Quality Development of Ballasted and Ballastless Track Superstructure and its Transition Areas - Libor Izvolt; Janka Sestakova; Michal Smalo (Communications - Scientific letters of the University of Zilina, 2016)
Securing durability of parameter quality of track alignment design and track geometry is a goal of each railway infrastructure manager. To accomplish this goal, various methods and procedures are applied, but they are all based on regular diagnostics, analysis of its results according to valid legislation and design and implementation of respective maintenance and repair works. The technological and economic optimization of planning and implementation of maintenance and repair works, based on prediction of quality development of railway track, is conditioned by precisely implemented and evaluated monitoring. In relation to these facts, the first part of the paper brings an overview of the problem of monitoring the ballastless structure and its transition areas around portals of the Turecky vrch tunnel by methods of complex diagnostics and quality evaluation of the structure including prediction of the structural quality development. The second part of the paper deals with the analysis of the detected errors of the ballastless track with specific focus on transition areas and on the ballasted track. It also summarizes the possibilities of elimination of these errors in building further sections with ballastless track. Modernization of these sections within modernization of ZSR infrastructure is a topical problem.